Assessing Pedagogical Competence Among Prospective Primary School Teachers: A Case Study - Harun, Askar (Journal of Education Review Provision, 2025)
With an emphasis on their self-perceived strengths and shortcomings in a variety of areas, such as topic knowledge, teaching tactics, classroom management, and technology integration, this study evaluates the pedagogical competency of aspiring primary school teachers.  Data were gathered from 150 participants in a teacher training program at a prestigious university using a quantitative survey approach.  According to the results, although the participants demonstrated a solid command of the subject matter, they also had modest opinions of their own teaching methods and classroom management, as well as a marked lack of confidence when it came to incorporating technology into their lesson plans.  These findings highlight the necessity for teacher training programs to better strike a balance between academic understanding and real-world application, especially when it comes to topics like digital tool use and classroom management.  According to the study, increasing possibilities for practical learning and incorporating technology-focused training could greatly raise future teachers' pedagogical proficiency.